1994
DOI: 10.1007/bf00966809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ca(II) ions on Mn(II) dynamics in chick glia and rat astrocytes: Potential regulation of glutamine synthetase

Abstract: Previous studies have demonstrated that in glia and astrocytes Mn(II) is distributed with ca. 30-40% in the cytoplasm, 60-70% in mitochondria. Ca(II) ions were observed to alter both the flux rates and distribution of Mn(II) ions in primary cultures of chick glia and rat astrocytes. External (influxing) Ca(II) ions had the greatest effect on Mn(II) uptake and efflux, compared to internal (effluxing) or internal-external equilibrated Ca(II) ions. External (influxing) Ca(II) ions inhibited the net rate and exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…There is evidence that brain GS is a Mn++ metalloprotein (Denman and Wedler, 1984; Wedler et al, 1982; Wedler and Ley, 1994; Wedler et al, 1994). Consistent with this conclusion are the observations that, regardless of whether the transferase activities or the biosynthetic activities of sheep brain GS were measured, the apparent K m for Mn ++ (∼20 µM) was approximately two orders of magnitude lower than the corresponding apparent K m for Mg(II) (1.7–3.5 mM) (Wedler and Toms, 1986).…”
Section: Regulation Of Gs In Astrocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that brain GS is a Mn++ metalloprotein (Denman and Wedler, 1984; Wedler et al, 1982; Wedler and Ley, 1994; Wedler et al, 1994). Consistent with this conclusion are the observations that, regardless of whether the transferase activities or the biosynthetic activities of sheep brain GS were measured, the apparent K m for Mn ++ (∼20 µM) was approximately two orders of magnitude lower than the corresponding apparent K m for Mg(II) (1.7–3.5 mM) (Wedler and Toms, 1986).…”
Section: Regulation Of Gs In Astrocytesmentioning
confidence: 99%
“…Consistent with this conclusion are the observations that, regardless of whether the transferase activities or the biosynthetic activities of sheep brain GS were measured, the apparent K m for Mn ++ (∼20 µM) was approximately two orders of magnitude lower than the corresponding apparent K m for Mg(II) (1.7–3.5 mM) (Wedler and Toms, 1986). In conjunction with the differential roles of divalent cations in activating brain GS (Meister, 1985), the finding that brain GS is a Mn metalloprotein, having a high affinity for Mn ++ , strongly suggests that intracellular levels of Mn ++ in astrocytes constitute one critical factor in regulating brain GS activity and flux (Wedler et al, 1994), because brain GS is largely astroglial in localization (Martinez-Hernandez et al, 1977). Brain levels of manganese become elevated in several neurodegenerative (e.g., Alzheimer’s disease and Parkinson’s disease) and metabolic (e.g., hepatic encephalopathy) diseases and in manganese toxicity (Lai et al, 1999; Lai et al, 2000).…”
Section: Regulation Of Gs In Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wedler and coworkers proposed that GS II is a Mn(II) containing enzyme [85], whereas Ginsburg and coworkers found that GS binds Mg(II) instead [74,76]. Wedler and Ley reported later [93], that the concentration of free cytoplasmic Mn(II) in chicken brain cells is near the K d for the GS^Mn(II) complex [87,93]. In the presence of mM Mg(II) and WM Mn(II), 20^30% of GS subunits were trapped with bound Mn(II) [93].…”
Section: Regulation By Metal Ionsmentioning
confidence: 99%
“…This increase in Ca 2+ blocks Mn 2+ uptake, prompting a release of mitochondrial Mn 2+ into the cytosol. Finally, high levels of cytosolic Mn 2+ in astrocytes activates glutamine synthetase, which removes excess glutamate (Wedler et al, 1994). However, excessive extracellular Mn 2+ can disrupt intracellular Ca 2+ signaling in astrocytes by competitively occupying Ca 2+ binding sites, thus interfering with mitochondrial Ca 2+ homeostasis (Farina et al, 2013).…”
Section: Manganese and Neuroinflammationmentioning
confidence: 99%